BERBAGAI SISTEM DALAM KEHIDUPAN YANG MEMPENGARUHI SISTEM PENDIDIKAN ISLAM - Nuryanti Siregar (Al-Muaddib : Jurnal Ilmu-Ilmu Sosial & Keislaman, 2019)
Abstract: Islam as a religion guided by revelation guides humanity to gain happiness in the word and the hereafter and to get that happiness must be with education. As a system, Islamic education is in the mids of various systems that exist in human life. It can be said that education is a system that is integrated with almost all systems in human life which involves many elements and parties that influence each other. Various system in life that effect the Islamic education system include economic, political, population, social and cultural system. Key Word: Various systems in the life that effect the Islamic education system (economic, political, population, social and cultural systems).